The correlation betwwen FEVI/ FVC with arm span to height or chest to waist ratio as an index of pulmonary function in healthy subject - Alnuami, Numan S. (Journal of the Faculty of Medicine Baghdad, 2012)
Background: the interpretation of pulmonary function tests relies on reference values corrected for age. Sex and height may be difficult to measure in patients with deformities of the thoracic cage or those who are unable to stand up propely.